Material descriptors for predicting thermoelectric performance. Issue 3 (16th January 2015) - Yan, Jun; Gorai, Prashun; Ortiz, Brenden; Miller, Sam; Barnett, Scott A.; Mason, Thomas; Stevanović, Vladan; Toberer, Eric S.
Abstract : A high throughput route to screen thermoelectric materials is developed and validated across a broad material set. Abstract : In the context of materials design and high-throughput computational searches for new thermoelectric materials, the need to compute electron and phonon transport properties renders direct assessment of the thermoelectric figure of merit ( zT ) for large numbers of compounds untenable. Here we develop a semi-empirical approach rooted in first-principles calculations that allows relatively simple computational assessment of the intrinsic bulk material properties which govern zT . These include carrier mobility, effective mass, and lattice thermal conductivity, which combine to form a semi-empirical metric (descriptor) termed β SE . We assess the predictive power of β SE against a range of known thermoelectric materials, as well as demonstrate its use in high-throughput screening for promising candidate materials.